Design of decentralized PID controller with the root locus method based on inverted decoupling for a TITO system - Wutthithanyawat, Chananchai; Wangnipparnto, Santi (Interdisciplinary Research Review, 2018)
Decentralized control is widely applied in several industrial plants and one of the decentralized techniques is the decoupled method used to reduce the interaction of diagonal loops and can be minimized TITO system into SISO system. This paper presents the decentralized PID controller design for TITO system using root locus method. An inverted decoupling approach is analyzed by an application of Wood–Berry distillation column process, when a FOPDT model of the process is considered. The results showed that by using the root locus method, the proper control parameters can be determined and the designed control system can regulate the process variables of TITO process. The designed decentralized PID controller based on inverted decoupling gave an effectiveness to maintain the controlled variables.